(untitled) (Bangladesh Agronomy Journal, 2021)
In search of alternative counter to harmful effects of chemical fertilizers on soils and environment, probiotic and organic manures-based fertilizer management options need to be evaluated. The experiments were designed as randomized complete block design (RCBD) consisting of three wheat varieties and nine soil amendment treatments. The result revealed that organic amendments had prominent and variable effects on studied parameters and statistically at par with chemical fertilizer. Some yield-associated parameters like spike length, spikeletsspike-1, fertile spikelets spike-1, grains spike-1, grains weight spike-1 and 1000-grain weight were significantly influenced by organic amendments. Moreover, grain yield and straw yield were increased73% and 27%, respectively under the treatment of poultry manure combination in comparison with control. In addition, the seed quality characters viz. germination, vigor index and total soluble protein content also exhibited significant improvement showing23%, 44%and 17%, respectively by poultry manure + vermicompost + green manure. The above findings showed that to apply poultry manure + vermicompost + green manure as an effective soil amendment option and to obtain good yield and quality seed of wheat. Bangladesh Agron. J. 2021, 24(1): 1-11